Single-molecule studies of transcription initiation - Duchi Llumigusin, D; Diego Duchi (2014)
Single-molecule Förster resonance energy transfer (smFRET) has emerged as an important tool for studying biological reactions. This thesis describes smFRET investigations into the mechanism of bacterial transcription initiation. We developed protocols to immobilize RNAP-DNA initiation complexes using vesicles and antibodies. We used these techniques to show that the transcription bubble conformation in immobilized complexes exhibits inter-molecular heterogeneity. We observed large FRET changes that we attribute to transcription bubble opening and closing dynamics. We found that σ70 region 3.2 (σR3.2) influences the kinetics of the bubble dynamics, which supports proposals that σR3.2 interacts with the transcription bubble template strand. We extended our investigations to RNA synthesis and were able to observe abortive initiation cycles directly. We observed RNAP pausing and backtracking for the first time in transcription initiation. We obtained data suggesting that σR3.2 stabilises short RNAs at the active centre and forms a barrier to the extension of RNAs longer than 5-nt in length. We extended our abortive initiation assay to observe signal changes that we attribute to promoter escape. Our data revealed the number of abortive cycles that occur prior to escape, the kinetics of promoter escape, and pausing events that may have some regulatory function. We investigated the conformational dynamics of the RNAP β' clamp and observed dynamic conformational changes between clamp-open and clamp-closed states. Our work confirms proposals that the clamp remains stably closed once the open complex (RPO) is formed. We investigated what affect the antibiotics Myxopyronin and Lipiarmycin have on the clamp conformation. Our results revealed that Myxopyronin traps the clamp in a closed conformation, while Lipiarmycin traps it in an open conformation. Overall, we made a number of novel observations that we believe advance our understanding of the mechanism of transcription. We hope that the discoveries reported here will direct future research efforts into RNAP function.